Modified Polyvinyl Alcohol Containing New Imides / Iron Oxide Nanoparticles :Synthesis , Characterization and Biological Evaluation - Saeed, Ruwaidah S.; Kawther Ayad Obead (Iraqi Journal of Pharmaceutical Sciences, 2025)
A series of new imides compounds[1-4] were synthesized from reaction of tetrachlorophthalic anhydride or nitro phthalic anhydride or malic anhydride or Succinic anhydride with 4-amino benzene thiol under fusion conditions. Chloroacetic acid has been added after compounds [1-4] reacted with distilled H2O and Na2CO3, producing compounds [5-8]. In benzene, compounds [5-8] also interacted with the thionyl chloride to produce [9-12]. Poly (vinyl alcohol) was chemically modified by reacting PVA with compounds [9-12] and dimethyl formamide to produce compounds [13-16]. Iron oxide nanoparticles (IONPs) are mixed with modified PVA [13-16] to create nanocomposites [17-20]. Spectral and analytical data from synthesized compounds, such as 1H-NMR, FTIR spectra and FESEM, were used to describe their structural characteristics. Two different types of bacteria : (G+) Bacillus cereus and E. coli (G-) have been used to test the antibacterial activity. Also, molecular docking is studied, where operations are used to predict the binding status of compound [9] with the enzyme and to calculate the free energy (ΔG) of the compounds prepared .Additionally, the anticancer activity of modified polyvinyl alcohol with new imides , modified polyvinyl alcohol with new imides and iron oxide NPs against the colon cancer cell line (HT29) was studied. MTT assay was utilized for estimating the anticancer activity as well as comparing it to that of normal cells WRL-68 (the human hepatic cell line).